Soluções por série e funções especiais - Teodoro, Wilkson Linhares (2017)
The present work aims to show the applicability of mathematics in the solution of physical problems. First, the behavior of a solution will be observed through local analysis. Next, demonstrate the solutions by power series and the special functions (Bessel, Hermite, Legendre and Laguerre) and, finally, the application by ordinary differential equation (ODE).